Efektivitas Kombinasi Bakteri Streptomyces sp Dengan Pestisida Nabati Daun Sirih Dan Daun Kelakai Terhadap Penyakit Antraknosa Pada Cabai Hiyung - Budi, Ismed Setya; Mariana, Mariana; Erlangga, Muhammad Dede (JURNAL PROTEKSI TANAMAN TROPIKA, 2025)
Chili is a commodity that experiences price fluctuations due to high demand. In 2021, cayenne pepper production in Indonesia will decrease by 8.09% compared to 2020. Anthracnose disease, caused by the fungus Colletotrichum sp., can reduce productivity by 5-30%, even causing crop failure. Biological control using Streptomyces sp. and plant-based pesticides such as betel leaves and kelakai leaves are environmentally friendly alternatives. This study evaluated the effectiveness of this combination against anthracnose in hiyung chilies. The results of the study showed that the application of the bacteria Streptomyches sp., the vegetable pesticide Kelakai Leaf, the vegetable pesticide Betel Leaf and their combination were able to reduce the incidence of anthracnose disease with disease incidence ranging from 15.05% -21.33% compared to controls whose disease incidence was 33.24%. The results of the analysis of the effectiveness of disease control showed that there were 4 treatments that were quite effective, Betel 54.72%, Streptomyces sp. 46.48%, combination of Betel and Streptomyces sp. 43.65%, and a combination of kelakai and Streptomyces sp 40.94%. The observation results also showed that the Betel biopesticide treatment was the best treatment in producing the highest crop of 30.56 cm and increasing the wet weight with a yield of 83.38 g, followed by the Kelakai treatment which also produced the highest yield of 82.03 g. Apart from that, all the treatments given were able to accelerate the flowering age of chilies by 56.08-57.52 days compared to the control of 58.28 days.